Efektivitas Pembelajaran PAI Dengan Model Snowball Throwing - Wulandari, Kartika; Narulita, Sari; Rachmat, Noor (Jurnal Studi Al-Qur'an, 2013)
The purpose of this study is to describe and analyze the Snowball Throwing learning model and to determine and describe the learning effectiveness of Snowball Throwing in PAI learning with models made by the teacher. This study uses the theory of effective learning conditions by Uzer Mohammad Usman. The method used in this research is descriptive and qualitative approach. By using the theory and methods above, this research concludes: application of Snowball Throwing learning modelis to look at the condition of effective learning is done well and the results of a questionnaire distributed show that73% of the learning is effective by using the Snowball Throwing PAI model, while 22% does not show the effectiveness of learning PAI with the model. The results are reinforced by the value of the average grade obtained through the values and practices that increase the value of summative score of 77 to 82. Three aspects are also developing capabilitiesie, cognitive, affective and psychomotor. Keywords: Effectiveness, Learning PAI, Snowball Throwing Model